The Approach of Christophorus Puciłowski SJ (1650–1707) to the Principle of fides in the Field of Politics - Grubliauskas, Matas (Senoji Lietuvos literatūra, 2024)
Christophorus Puciłowski, a Jesuit professor of rhetoric and philosophy at Vilnius University at the end of the 17th century, is barely known in the field of early Lithuanian literature. He has still not received proper attention from philologists or philosophers, although pieces of his work have reached our times. Among these is a brochure for the play Victoria Mariae (1684), and notes from his course in politics taught during the 1691–1692 academic year at Vilnius University. Both the play and the notes are examined, for they represent the activities of Societas Jesu in the context of the political circumstances. The first marks an important event both for the Commonwealth of Two Nations and the entire Christian world: King Johannes III Sobieski’s victory over the Turks near Vienna. The second is a course that concerns the governance, virtues and aims of a Christian state. In this article, the emphasis is placed on trying to reconstruct Puciłowski’s model of society based on the principle of fides. These two sources are compared with other similar sources: firstly, in the case of the course, with two other courses on politics; and secondly, in the case of the play, with other literature written to mark the victory. The views of the Vilnius professor about contemporary political and social life will be reconstructed.
Keywords: political thought; Christophorus Puciłowski; Praelectiones politicae; Victoria Mariae; fides; Jesuits; 17th-century neo-Latin literature